Cyclic GMP‐AMP synthase contributes to epithelial homeostasis in intestinal inflammation via Beclin‐1‐mediated autophagy. Issue 5 (28th March 2022) - Khan, Sidrah; Mentrup, Heather L.; Novak, Elizabeth A.; Siow, Vei Shaun; Wang, Qian; Crawford, Erin C.; Schneider, Corinne; Comerford, Thomas E.; Firek, Brian; Rogers, Matt B.; Loughran, Patricia; Morowitz, Michael J.; et al.
Abstract: Inflammatory bowel disease (IBD) represents a set of idiopathic and chronic inflammatory diseases of the gastrointestinal tract. Central to the pathogenesis of IBD is a dysregulation of normal intestinal epithelial homeostasis. cGAS is a DNA‐sensing receptor demonstrated to promote autophagy, a mechanism that removes dysfunctional cellular components. Beclin‐1 is a crucial protein involved in the initiation of autophagy. We hypothesized that cGAS plays a key role in intestinal homeostasis by upregulating Beclin‐1‐mediated autophagy. We evaluated intestinal cGAS levels in humans with IBD and in murine colonic tissue after performing a 2% dextran sulfate sodium (DSS) colitis model. Autophagy and cell death mechanisms were studied in cGAS KO and WT mice via qPCR, WB analysis, H&E, IF, and TUNEL staining. Autophagy was measured in stimulated intestinal epithelial cells (IECs) via WB analysis. Our data demonstrates cGAS to be upregulated during human and murine colitis. Furthermore, cGAS deficiency leads to worsened colitis and decreased levels of autophagy proteins including Beclin‐1 and LC3‐II. Co‐IP demonstrates a direct binding between cGAS and Beclin‐1 in IECs. Transfection of cGAS in stimulated HCT‐116 cells leads to increased autophagy. IECs isolated from cGAS KO have diminished autophagic flux. cGAS KO mice subjected to DSS have increased cell death and cleaved caspase‐3. Lastly, treatment of cGAS KO mice with rapamycin decreased the severity of colitis. Our data suggest that cGAS maintains intestinal epithelial homeostasis during human IBD and murine colitis by upregulating Beclin‐1‐mediated autophagy and preventing IEC death. Rescue of autophagy can attenuate the severity of colitis associated with cGAS deficiency.